2011
DOI: 10.1111/j.1445-2197.2010.05602.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nasendoscopic-assisted cautery versus packing for the treatment of epistaxis

Abstract: We have shown NC for epistaxis to be an effective treatment. In our study, it was associated with a significantly reduced hospital admission, complication rate and with no re-presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
11
0
3
Order By: Relevance
“…Its prolonged use may increase the risk of bacterial colonisation. [11] Despite using Merocel ® , one patient of 33 developed Grade 1 pressure ulcers which implies that adjunctive steps are needed to reduce the occurrence and severity of pressure ulcers. These may include using proper size of ETT, appropriate fixation and positioning of the tube, use of soft flexible nasotracheal tube, repeated assessment of the skin during surgery, and avoidance of repositioning of tube and frequent head movement.…”
Section: Discussionmentioning
confidence: 99%
“…Its prolonged use may increase the risk of bacterial colonisation. [11] Despite using Merocel ® , one patient of 33 developed Grade 1 pressure ulcers which implies that adjunctive steps are needed to reduce the occurrence and severity of pressure ulcers. These may include using proper size of ETT, appropriate fixation and positioning of the tube, use of soft flexible nasotracheal tube, repeated assessment of the skin during surgery, and avoidance of repositioning of tube and frequent head movement.…”
Section: Discussionmentioning
confidence: 99%
“…Of 4 retrospective series study; 3 [20][21][22] favoured the early surgical intervention where as older retrospective case series by Schaitkin et al [23] showed that surgery was associated with more complications. In the included studies for this systematic review; failure rates (re-bleed after primary intervention for posterior epistaxis) of packing were 23% to 53% and for early surgical intervention were 0% to 11%.…”
Section: Discussionmentioning
confidence: 99%
“…The both males and females from all ethnical backgrounds were included 2. Studies that compared the management by the occlusion of the arteries by percutaneous embolisation were excluded Although the comparison was not mainly for posterior epistaxis the retrospective study by Ha et al [22] shows the success rate (no re-bleeds) with early management of epistaxis patients with Nasoendoscopic cautery (NC) was 100% compared to 68% in conventional treatment (CT) group. Also NC group had had no complications while CT group had 2 patients with dysrhythmia; 1 required transfusion for anemia; 1 myocardial infarction; 1 had pack dislodgement.…”
Section: -Participantsmentioning
confidence: 99%
“…We read with great interest the article of Ha et al 1 . published recently in ANZ Journal of Surgery and would like to make comments on this study.…”
mentioning
confidence: 94%